2012
DOI: 10.1177/0148607112445900
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Nutrition Status and Postoperative Outcome in Elderly General Surgery Patients

Abstract: This systematic review revealed only 2 preoperative parameters to predict postoperative outcome in elderly general surgery patients: weight loss and serum albumin. Both are open to discussion in their use as a preoperative nutrition parameter. Nonetheless, serum albumin seems a reliable preoperative parameter to identify a patient at risk for nutrition deterioration and related complicated postoperative course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
1
19

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(113 citation statements)
references
References 41 publications
0
89
1
19
Order By: Relevance
“…van Stijn et al [15] performed a systematic review over 10 years to assess the role of evaluation of preoperative nutrition parameters in predicting postoperative outcomes in elderly patients. They showed 15 appropriate articles out of 463 total articles and found great heterogeneity in the parameters to evaluate preoperative nutritional status and postoperative outcomes.…”
Section: Nutritional Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…van Stijn et al [15] performed a systematic review over 10 years to assess the role of evaluation of preoperative nutrition parameters in predicting postoperative outcomes in elderly patients. They showed 15 appropriate articles out of 463 total articles and found great heterogeneity in the parameters to evaluate preoperative nutritional status and postoperative outcomes.…”
Section: Nutritional Assessmentmentioning
confidence: 99%
“…They showed 15 appropriate articles out of 463 total articles and found great heterogeneity in the parameters to evaluate preoperative nutritional status and postoperative outcomes. They found only two significant preoperative predictors of postoperative outcomes: serum albumin and greater than 10% weight loss in the last 6 months [15]. A nomogram, based on the American College of Surgeons National Surgical Quality Program 10,392 elderly patients' database, recently confirmed that preoperative weight loss is statistically responsible for anastomotic leak after CRC surgery [16].…”
Section: Nutritional Assessmentmentioning
confidence: 99%
“…Furthermore, NS, assessed either by the MNA-score, recent weight loss, body mass index (BMI) or serum albumin levels, are known prognostic factors of survival and response to chemotherapy in cancer patients [5,8,35]. Data on the predictive ability of nutritional markers on postoperative outcomes in the elderly general surgery and hip surgery patient populations are scarce and nutritional markers are operationalized in several ways, according to a systematic review including 15 studies [36]. Serum albumin is a frequently investigated nutritional M A N U S C R I P T…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…However, serum albumin might be merely a marker of inflammatory metabolism rather than a pure representative of nutritional status in surgical patients [36]. Three included studies used a nutritional questionnaire, such as the MNA or the food frequency questionnaire.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In einer großen Kohortenstudie hat sich bei abdominalchirurgischen Patienten eine verminderte Nahrungsaufnahme in der Woche vor der Krankenhausaufnahme als ein noch besserer Risikoprädiktor gezeigt [19]. FĂźr älte-re chirurgische Patienten (> 65 Jahre) konnten in einer systematischen Über-sicht von 15 Studien aus den Jahren 1998 bis 2008 nur der Gewichtsverlust und das Serumalbumin als prädiktive Parameter fĂźr postoperative Komplikationen gefunden werden [36]. Dies hat sich in einer ganz aktuellen prospektiven skandinavischen Studie bei Patienten mit Operationen im oberen Gastrointestinaltrakt mit einem Gewichtsverlust von sogar > 5 % und einem Serumalbumin < 35 g/l bestätigt [1].…”
Section: Erkennung Eines Metabolischen Risikosunclassified